Environmental performance indicators for energy sector industry : a thesis presented in fulfilment of the requirements for the degree of Masters in Applied Science in Natural Resource Management at Massey University - Kissick, Joanne Terese (Massey University, 2000)
Mounting evidence regarding the degradation of our environment and a growing sense of shared responsibility has provided the impetus to develop multilateral environmental agreements to address global environmental problems. Concerns regarding unsustainable energy consumption and production patterns have also underscored the need to improve environmental monitoring. This research provides an analysis of the role and status of environmental performance indicators for energy sector industry in New Zealand. The environmental indicators considered are those that are directly aligned to energy consumption and production patterns. In order to be able to identify and isolate the range of issues associated with energy consumption and production patterns, it is necessary to understand both the factors that influence energy use and the effects that arise. Factors that can be utilised as environmental indicators include, energy efficiency, energy intensity, energy fuel mixes and energy prices, and the carbon dioxide emissions associated with energy use. Much progress has been made at a national and international level in the development and use of environmental indicators for energy sector industry. The UN, OECD, and Natural Resources Canada all utilise the above-described environmental indicators to assess energy consumption and production patterns. This progress provides useful insight for the MfE in the development of their national energy indicators. The MfE's energy indicators when introduced will prove a fundamental monitoring tool for policy makers in New Zealand. Environmental indicators will enable policy makers at either a local, national or international level to be able to accurately monitor and evaluate the environmental consequences associated with energy consumption and production patterns (including those of energy sector industry). From this monitoring, policy makers will be able to assess the effectiveness of their environmental policy frameworks. In doing so, policy makers will avoid misinterpreting or inappropriately responding to their environmental policy frameworks or obligations.
Keywords: New Zealand; Environmental indicators; Environmental policy; Energy policy